2005
DOI: 10.1021/np050096g
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes from the Red Alga Laurencia tristicha

Abstract: Seven new sesquiterpenes (1-7), together with seven known sesquiterpenes, aplysin (8), aplysinol (9), gossonorol (10), 7,10-epoxy-ar-bisabol-11-ol (11), 10-epi-7,10-epoxy-ar-bisabol-11-ol (12), johnstonol (13), and laurebiphenyl (14), have been isolated from the red alga Laurencia tristicha. The structures of new compounds were established as laur-11-en-2,10-diol (1), laur-11-en-10-ol (2), laur-11-en-1,10-diol (3), 4-bromo-1,10-epoxylaur-11-ene (4), cyclolauren-2-ol (5), laurentristich-4-ol (6), and ar-bisabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 32 publications
1
74
0
Order By: Relevance
“…Compound 112, having a novel rearranged cyclolaurane skeleton was also reported recently from L. okamurai [78]. Compound 114 exhibited moderate cytotoxicity against several human cancer cell lines, while all other compounds were inactive [12]. The Chinese species L. tristicha produced aplysin-9-ene (115), epiaplysinol (116) and debromoepiaplysinol (117).…”
Section: Laurane Skeleton Sesquiterpenesmentioning
confidence: 74%
See 3 more Smart Citations
“…Compound 112, having a novel rearranged cyclolaurane skeleton was also reported recently from L. okamurai [78]. Compound 114 exhibited moderate cytotoxicity against several human cancer cell lines, while all other compounds were inactive [12]. The Chinese species L. tristicha produced aplysin-9-ene (115), epiaplysinol (116) and debromoepiaplysinol (117).…”
Section: Laurane Skeleton Sesquiterpenesmentioning
confidence: 74%
“…In 2007, L. microcladia (Chios Is., North Aegean Sea) afforded the hydroxyl derivative of β -bisabolene, (66) [60], while, (5S)-5-acetoxy-β -bisabolene (67), was isolated, recently, from L. okamurai Yamada [61]. L. tristicha (Naozhou Island, China) yielded ar-bisabol-9-en-7,11-diol (68) [12]. On the other hand, L. scoparia (S˜ao Paulo, Brazil) was the source of compounds (69)(70)(71).…”
Section: Bisabolane Skeleton Sesquiterpenesmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Another study indicated that a new sesquiterpene from the fruits of Daucus carota also displayed weak cytotoxic activity against BGC-823, with an inhibition rate of 13.3%. 28 We hypothesized that (+)-chabranol may disrupt DNA synthesis and reduce mitotic activity in BGC-823 cells, both of which Transmission electron microscopic analysis of the subcellular structure showed that cells exposed to (+)-chabranol were filled with autophagy vacuoles and lipid droplets.…”
Section: Antitumour Effect Of (+)-Chabranolmentioning
confidence: 99%